Entrepreneurial Developments and Challenges in the Sud Muntenia Region of Romania - Marioara Iordan; Mihaela-Nona Chilian (European Regional Science Association (ERSA), 2011)
Entrepreneurship is crucial for the economic development of a region. Using entropy, cluster and shift-share analysis techniques, the authors present a detailed picture of the entrepreneurial milieu of the Sud Muntenia region of Romania, pointing both towards the presence of an overall development process, and also to inter-county and intra-county sectoral imbalances, evolutionary discrepancies and lack of adequate use of territorial resources. Policy recommendations are proposed to address the future challenges for the balanced development of the Sud Muntenia region of Romania.
Keywords: O18; R11; R12; R30; 330; entrepreneurship; territorial development; regional business demography; sectoral structure; regional policy